2018
DOI: 10.1111/mms.12511
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, demography, and behavior of North Atlantic right whales (Eubalaena glacialis) in Cape Cod Bay, Massachusetts, 1998–2013

Abstract: The occurrence of North Atlantic right whales (Eubalaena glacialis) in Cape Cod Bay was documented during aerial surveys between 1998 and 2013. The seasonal occurrence remained relatively unchanged during the study, spanning the January through mid-May timeframe. The number of individual whales visiting the Bay was positively correlated with the increasing Best Cataloged Estimate (BCE), the number of photographed whales alive, with a maximum in 2011 of 56.9% (n 5 277) of BCE. However, the rate of increase in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 30 publications
7
31
0
Order By: Relevance
“…Despite the apparently declining population in the last 3 years of this study, we found that the mean acoustic presence of right whales in MB was higher during this period than in the first 3 years, at all times of year (Figure ). This finding is consistent with increased winter and spring use of CCB during these years, suggesting that right whale habitat preferences have changed during the period of this study (Mayo et al, ). This increased use of the Massachusetts–CCB area is part of a broader pattern of shifting habitat use observed throughout the Gulf of Maine and adjacent regions, compared to patterns typically observed during the previous three decades (Davis et al, ; Pace et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Despite the apparently declining population in the last 3 years of this study, we found that the mean acoustic presence of right whales in MB was higher during this period than in the first 3 years, at all times of year (Figure ). This finding is consistent with increased winter and spring use of CCB during these years, suggesting that right whale habitat preferences have changed during the period of this study (Mayo et al, ). This increased use of the Massachusetts–CCB area is part of a broader pattern of shifting habitat use observed throughout the Gulf of Maine and adjacent regions, compared to patterns typically observed during the previous three decades (Davis et al, ; Pace et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…The peak season of 2010 was notable in having a mean hourly presence that was much lower than that of any other year (Figures and ). This pattern was strikingly similar to that observed in the number of identified right whales observed per unit of aerial survey effort in CCB in 2010 (Mayo et al, ). Densities of zooplankton genera ( Calanus , Pseudocalanus , and Centropages ) on which right whales feed were also anomalously low in 2010 in CCB (Stamieszkin et al, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Right whales are classified as Endangered under the US Endangered Species Act and by the International Union for the Conservation of Nature (Reilly et al 2012). Every year, from January through May (hereafter the season), right whales return to CCB, an important feeding ground for this species (Mayo & Marx 1990, Clark et al 2010, Mayo et al 2018, which has been designated as critical habitat for right whales (NOAA 1994). The main copepod taxa on which right whales feed are abundant in these waters and whale diving behavior is influenced by the copepods' vertical distribution, which varies seasonally (Mayo & Marx 1990, Baumgartner & Mate 2003, Parks et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1997, the Center for Coastal Studies has conducted systematic aerial line-transect surveys to monitor right whale habitat use in CCB (Mayo et al 2018). During the surveys, photographs of individual whales are collected and used for health assessments (Pettis et al 2004, Rolland et al 2016, reporting and monitoring entanglements in fishing gear (Knowlton et al 2012, Robbins et al 2015, and population studies (Pace et al 2017).…”
Section: Introductionmentioning
confidence: 99%